Ecological-health risk assessments of heavy metals (Cu, Pb, and Zn) in aquatic sediments from the ASEAN-5 emerging developing countries: a review and synthesis - Chee, Kong Yap; Al-Mutairi, Khalid Awadh (MDPI, 2021)
The ASEAN-5 countries (Malaysia, Indonesia, Thailand, Philippines, and Vietnam) of the Association of Southeast Asian Nations as a group is an ever-increasing major economy developmental hub in Asia besides having wealthy natural resources. However, heavy metal (HM) pollution in the region is of increasing environmental and public concern. This study aimed to review and compile the concentrations of Cu, Pb, and Zn in the aquatic sediments of the ASEAN-5 countries published in the literature from 1981 to February 2021. The mean values of Cu, Pb, and Zn in aquatic sediments were elevated and localized in high human activity sites and compared to the earth’s upper continental crust and reference values. Based on 176 reports from 113 publications, the ranges of concentrations (mg/kg dry weight) were 0.09–3080 for Cu, 0.37–4950 for Zn, and 0.07–2666 for Pb. The ecological risk (ER) values ranged from 0.02–1077 for Cu, 0.01–95.2 for Zn, and 0.02–784 for Pb. All reports (100%) showed the Zn ER values were categorized as being between ‘low potential ecological risk’ and ‘considerable potential ecological risk’. Almost all Cu ER values (97.7%) also showed similar ranges of the above two risk categories except for a few reports. The highest Cu level (3080 mg/kg dry weight) was reported from a mine-tailing spill in Marinduque Island of the Philippines with ‘very high ecological risk’. In addition, drainage sediments in the western part of Peninsular Malaysia were categorized as Cu ’high potential ecological risk’. Almost all reports (96%) showed Pb ER values categorized as between ‘low potential ecological risk’ and ‘moderate potential ecological risk’ except for a few reports. Six reports showed Pb ER values of ‘considerable potential ecological risk’, while one report from Semarang (Indonesia) showed Pb ER of ‘very high ecological risk’ (Pb level of 2666 mg/kg dry weight). For the ingestion and dermal contact pathways for sediments from the ASEAN-5 countries, all non-carcinogenic risk (NCR) values (HI values 1.0) for Cu, Pb, and Zn reflected no NCR. The ER and human health risk assessment of Cu, Pb, and Zn were compared in an integrative and accurate manner after we reassessed the HM data mentioned in the literature. The synthesis carried out in this review provided the basis for us to consider Cu, Pb, and Zn as being of localized elevated levels. This provided evidence for the ASEAN-5 group of countries to be considered as being a new socio-economic corridor. Beyond any reasonable doubt, an ever-increasing anthropogenic input of HMs is to be expected to a certain degree. We believe that this paper provides the most fundamental useful baseline data for the future management and sustainable development of the aquatic ecosystems in the region. Lastly, we claim that this review is currently the most up-to-date review on this topic in the literature.